The Impact of Android Applications on Hajj Pilgrims' Comprehension: A Technological Approach to Religious Guidance - Rakhmadi, Aris; Rochmijatun, Siti; Nurgiyatna, Nurgiyatna; Triyono, Agus (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Hajj is a fundamental pillar of Islam that requires pilgrims to perform a series of complex rituals with precision and understanding. However, many prospective pilgrims struggle to retain and apply the necessary knowledge using traditional lecture-based instruction alone. With the rise of digital tools, mobile applications have emerged as a promising supplement to enhance religious education. This study investigates the effectiveness of two Android-based applications—Haji Pintar and Kawal Haji—in improving Hajj pilgrims' comprehension, retention, and confidence. Employing a quasi-experimental design, 133 participants were divided into a control and experimental group, with the latter incorporating mobile-assisted learning. Pre- and posttest assessments, along with surveys and semi-structured interviews, were conducted to evaluate outcomes. Results revealed that the experimental group showed significantly higher knowledge retention and confidence compared to the control group. Qualitative findings further highlighted how features such as video tutorials and interactive guides enhanced learners' emotional preparedness and engagement. This research makes a unique contribution to the literature by providing empirical evidence of the impact of mobile learning in religious contexts, utilizing mixed methods to measure comprehension outcomes. The findings offer practical implications for developing inclusive digital Hajj training, particularly for elderly users, and call for collaboration with religious institutions in designing structured, mobile-based curricula. Theoretically, the study reinforces the relevance of technology-assisted, self-paced models in Islamic education.